Towards Achieving Smart Healthcare Through the Adoption of Information Technology - Mahar Nooruldeen Saaed; Osamah Fadhil Taher; Adnan Salih Mahmood; Suhair Abd Dawwod; Ramadan Mahmood Ramo; Muhammad Mustafa Hussien (Universitas Negeri Semarang, 2026)
Purpose: The study focuses on the impact of Virtual Reality as a therapeutic technology in the context of Smart Healthcare on the rehabilitation of hand amputees and the ability of out-patients to gain computer access in a cost-effective manner. Methods: A qualitative, descriptive bibliometric survey of the literature was undertaken, utilizing peer-reviewed literature relevant to the integration of virtual medical care (V-Med) with the IoT, EHR, and CDSS. The literature examined was categorized into two analytical domains - physical and clinical opportunities and technical challenges. Results: The evidence suggests that cloud focused Virtual Reality (VR) helps people with Phantom limb pain and reduces the time required for amputees to achieve the adaptation to a prosthesis. The disadvantages of VR technology will only be realized when VR technology, EHR and the Internet of Everything (IoE) systems coalesce. This is where the central issue of technical feasibility lies. Novelty: The presentation here outlines a shift in attitude towards Virtual Reality. Rather than isolating it from a continuum encompassing all virtualization in the cloud with amputee rehabilitation modalities, we embrace it. We propose a framework that integrates cloud-based IoT wearables, EHRs, and CDSS into a Smart Healthcare ecosystem, thus outlining a feasible, affordable scalable virtual rehabilitation path.